VIDEO MAPPING AS A PHENOMENON OF PUBLIC CULTURAL SPACE - Ольховой, О.; Лысенко, Е. (SWorldJournal, 2021)
The article analyzes the practical experience of forming public spaces with the use of augmented reality; in particular, special attention is focused on examples of the use of video mapping in Ukraine. Techniques for designing innovative socio-cultural s